Preservation of Limb Growth Potential in Treatment of Pediatric Osteosarcoma Around the Knee: Research Progress and Future Prospect - Zhiqing ZHAO; Wei GUO; Taiqiang YAN (Zhongliu Fangzhi Yanjiu)
With the development of imaging technology, advancements in surgical techniques, application of multidrug chemotherapy, and collaboration in postoperative rehabilitation, the local recurrence rate and survival of patients with osteosarcoma after limb-sparing surgery are comparable to those of patients after amputation. The area around the knee joint, including the distal portion of the femur and the proximal portion of the tibia, is a typical site of involvement for osteosarcoma. Metal prosthetic replacement is the most common method to reconstruct bone defect after tumor resection, which provides rapid recovery of limb function after surgery. This article mainly discusses the clinical challenge of limb-saving technology for pediatric osteosarcoma. It also describes how to optimally preserve the growth potential of children’s affected limbs to reduce the future limb length discrepancy. Limb-sparing technology is one of the most cutting-edge precision medical technologies in the industry. Sacrificing or preserving the knee joint according to the distance between the tumor of distal femur and the epiphyseal growth plate, retaining the potential for limb growth, 3D-printed reconstructed prostheses are becoming increasingly popular. This article summarizes the progress and future development in the surgical treatment of pediatric osteosarcoma around the knee to offer insights for orthopedic treatment of this disease.